Effect of Solvent Type on the Antibacterial Activity of Trigona laeviceps Propolis Extract - Intan Nurul Azni; Dede Robiatul Adawiyah; Uswatun Hasanah; Nancy Dewi Yuliana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Propolis is a resinous compound which is mixed with saliva, wax, and other metabolic products of bees. One of the benefits of propolis is as an antimicrobial agent. The objective of this research was to determine antibacterial activity Trigona laeviceps bees propolis originating from Bogor West Java extracted with various solvents (water, ethanol, hexane). The tested bacteria consist of 2 Gram negative and 5 Gram positive bacteria. The raw propolis were characterized for gum, tannin, flavonoid, alkaloid, saponin, total phenol content, and proximate composition. Antibacterial activity was tested using the disc diffusion method. The data were analyzed using the ANOVA test and further tested with the Duncan test at a significance level of 5%. The results showed that the largest component of the sampel was lipid (65.47%). Raw propolis contains phenol (3.08 mg/g), tannin (34.45 mg/g), and flavonoid (21.88 mgQCE/g). The highest yield of propolis extract was obtained with hexane solvent (51.03%), followed by ethanol (18.17%), and water (15.58%). All propolis extracts did not have an inhibition zone against Gram-negative bacteria, but did for Gram-positive bacteria. The propolis extract using ethanol showed the highest diameter inhibition zone (16.92 mm). The finding of this study may be utilized to improve Trigona laeviceps propolis quality in Bogor.